MENINGKATKAN KUALITAS KEGIATAN ROHANI ISLAM (ROHIS) DI MADRASAH ALIYAH: STRATEGI DAN TANTANGAN - Deny Ahmad Jaelani; Nadia Islamadina Alamsyah; Muhammad Adam; Tesa Sekarwati; Meliawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of improving the quality of Islamic spiritual activities (Rohis) as a means of fostering students’ religious character in Madrasah Aliyah. However, in practice, Rohis activities still face several challenges, including low student interest, limited facilities, the influence of technological developments, and time constraints. This study aims to analyze the strategies used to improve the quality of Rohis activities and to identify the challenges encountered in their implementation. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving Rohis supervisors, administrators, and students. The data were analyzed through systematic processes of data reduction, categorization, and interpretation. The findings reveal that the improvement of Rohis activity quality is achieved through the development of varied and innovative programs, the application of interactive learning methods, and the utilization of digital media. In addition, the active role of supervisors and student administrators significantly contributes to the effectiveness of the activities. Rohis activities also show positive impacts on students, particularly in increasing participation, discipline in worship, and religious attitudes in daily life. Despite these achievements, several challenges remain, requiring continuous innovation and institutional support. Therefore, Rohis activities play a crucial role in shaping students’ religious character and need to be continuously developed in accordance with contemporary educational demands.